APLIKASI PUPUK HAYATI DAN KANDANG UNTUK PENGENDALIAN LALAT BIBIT PADA TANAMAN KEDELAI - Hasnah Hasnah; Susanna Susanna (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2010)
The objectives of this research were to find out dosages of biofertilizer and manure which was the most effective to control bean fly (A. phaseoli). This research was carried out at Cot Cut Village, District of Kuta Baro, Aceh Besar, from September to December 2008. This research used a factorial randomized complete block design with two factors: biofertilizer (H) and manure (K). Dosages of biofertilizer were H1= 2,8 L ha-1, H2= 3,5 L ha-1, H3= 4,2 L ha-1, and H4= 4,9 L ha-1. Dosages of manure fertilizer were K1= 2,8 ton ha-1, K2= 5,6 ton ha-1 and K3= 8,4 ton ha-1. The result showed that application of biofertilizer was more effective than that of manure fertilizer to percentage rates of the attacked plant. However, both biofertilizer and mature fertilizer exerted significant effects to percentage of plant death, plant dwarf, number of larva and pupa, and dry seed weight per plant. Application of biofertilizer at 4,9 L ha-1 and manure fertilizer at 8,4 ton ha-1 reduced percentages of plant death up to 86% and 83%, respectively.